2013
DOI: 10.4293/108680813x13693422520044
|View full text |Cite
|
Sign up to set email alerts
|

Suture Versus Tack Fixation of Mesh in Laparoscopic Umbilical Hernia Repair

Abstract: These authors suggest there is no difference in postoperative complication rates in suture versus tack mesh fixation in laparoscopic umbilical hernia repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…Bulging can be a serious problem, demanding a new procedure [26], however, this it is not our experience that this is very common, as for most of the reported bulges in our study, patients were oblivious and bulging was discovered during physical examination. The use of absorbable suture for defect closure in our study was apparently counter effective in PH and with no added benefit in IH, but this is so far the only RCT published on the question of IPOM+ and only retrospective comparative studies, and supporting IPOM+, have been published [155,156] The other randomization arm: mesh fixation with Protack in Double Crown formation [157] vs. corner anchor suture and one row of tackers did not shown any difference on any parameter, substantiated by other studies [150,[158][159][160]. The increased use of tacker-only fixation has been controversial and is still countered by experts.…”
Section: Comparison Of Lvhr In Ph and Ihsupporting
confidence: 76%
“…Bulging can be a serious problem, demanding a new procedure [26], however, this it is not our experience that this is very common, as for most of the reported bulges in our study, patients were oblivious and bulging was discovered during physical examination. The use of absorbable suture for defect closure in our study was apparently counter effective in PH and with no added benefit in IH, but this is so far the only RCT published on the question of IPOM+ and only retrospective comparative studies, and supporting IPOM+, have been published [155,156] The other randomization arm: mesh fixation with Protack in Double Crown formation [157] vs. corner anchor suture and one row of tackers did not shown any difference on any parameter, substantiated by other studies [150,[158][159][160]. The increased use of tacker-only fixation has been controversial and is still countered by experts.…”
Section: Comparison Of Lvhr In Ph and Ihsupporting
confidence: 76%
“…13 Riley KK et al in their study titled suture versus tack fixation of mesh in laparoscopic umbilical hernia repair didn't find any differences in their result between suture and tack fixation of mesh for LVHR. 21 Here, result of this study also didn't find any shortfall in surgical outcome of these tack only mesh fixation after comparing with result of any other case series reported earlier in respect of LVHR. 22,23 At last, as reported earlier also, one thing is absolutely true that LVHR is a better way of repair for abdominal ventral hernia with less morbidity and recurrence in comparison to open technique.…”
Section: Discussionsupporting
confidence: 60%
“…It has been found that these staples could cause chronic pain. 8 To overcome this, the mesh can be left in place without fixation or it can be fixed with fibrin glue. Both methods although appear effective their impact on chronic pain is unclear.…”
Section: Mesh Fixationmentioning
confidence: 99%